Medium dose ultraviolet A1 phototherapy and mRNA expression of interleukin 8, interferon γ, and chemokine receptor 4 in acute skin lesions in atopic dermatitis - Bogaczewicz, Jarosław; Malinowska, Karolina; Sysa-Jedrzejowska, Anna; Wozniacka, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Mechanisms responsible for UVA1 efficacy in atopic dermatitis (AD) are not fully elucidated. Aim: To investigate IL-8, CCR-4, and IFN-γ mRNA expression in AD before and after UVA1, to identify correlations among them, and to determine whether and to what degree mRNA expression is influenced by UVA1. Material and methods : Twenty-five patients with AD underwent medium dose UVA1-phototherapy at daily dosages of 10, 20, 30, 45, and then continuing 45 J/cm 2 up to 20 days, from Monday to Friday for 4 weeks. Before and after UVA1, biopsies from acute skin lesions were studied using reverse-transcription and RT-PCR. Results : The levels of CCR-4 mRNA correlated with those of IFN-γ, both before and after UVA1 phototherapy (p < 0.05). A significant correlation was found after UVA1 between mRNA levels of IL-8 and IFN-γ (p < 0.05). After UVA1 an increase in IL-8 mRNA expression in comparison to the baseline assessment (p = 0.02) was found, while no significant difference was revealed in the expression of CCR-4 and IFN-γ mRNA. UVA1 improved both SCORAD and severity of AD (p < 0.001). SCORAD and the severity of AD did not correlate with the degree of expression of measured cytokine mRNA, neither before nor after UVA1. Conclusions : CCR-4 is expressed in parallel with IFN-γ in acute skin lesions of patients with AD both before and after UVA1 phototherapy. UVA1 significantly improves SCORAD index, lessens the severity of AD and increases the expression of IL-8, with no direct effects on other studied molecules.